Keunggulan Komparatif Indonesia Pada Sepuluh Komoditi Unggulan ASEAN Tahun 1997 - 2009 - Wellyanti, Briliana (Jurnal Ekonomi Kuantitatif Terapan; 2015: Vol. 8, No. 1, Februari 2015 (pp. 1-112)DO - 10.24843/JEKT.2015.v08.i01.p10, 2015)
Economic growth is one indicator of a country's welfare. The massive economic growth is the goal of whole country. One way to improve economic growth is international trade. Indonesia is one country with an open economy so that it can be said Indonesia also commit the international trade. One of Indonesia's largest export destination is the ASEAN countries. There are some commodities that have the largest contribution in exports among ASEAN countries. Commodities are grouped into the Top Ten ASEAN Trade Commodity. Top Ten ASEAN Trade Commodity is ten most commodities needed by ASEAN countries seen from the value of exports and imports that occur between ASEAN countries in the period 1997-2009. Departing from the above background, the purpose of this study is to see how the development of the Top Ten ASEAN Trade Commodity during the period 1997-2009, how the level of comparative advantage in the Top Ten ASEAN Indonesia Commodity Trade in the period 1997-2009 and determine the development of the Top Ten ASEAN Trade Commodity Indonesia in the period 1997-2009 based on the analysis of RTA (Relative Revealed Trade Advantage). The method used in this research is descriptive analysis method and analysis of comparative advantage / RTA analysis (Relative Revealed Trade Advantage). Based on the analysis of comparative advantage, it can be concluded that the commodities which have a comparative advantage based on the analysis of the RTA is a commodity with HS15 code (fats and animal or vegetable oils and their cleavage products; processed edible fats; animal or vegetable waxes) and commodities with HS Code 71 (natural pearls, cultured pearls, precious or semi-precious stones, precious metals, precious metals, imitation jewelery, coins). The leading commodities (HS codes 71 and 15) is at the stage of maturity / growth (advanced). This shows that Indonesia can meet domestic demand for commodities 71 and 15 and able to export to meet the needs of overseas.
Keywords: comparative advantages, top ten ASEAN trade commodity, RCA, RCDA, RTA, ISP